A study on the predictability of the tooth form of the maxillary central incisors using the facial outline form among UP College of Dentistry Clinicians - Mangila, Ma. Agnes Veronica R.
Tooth selection far the replacement of teeth for complete den-tures has long been a problem among dental practitioners. At present, there is still no universally accepted method for tooth selection. One of the theories followed by many dentists is Williams' Law of Harmony which states that tooth form follows the facial outline form. This study seeks to establish the predicta bility of the tooth, form by using the facial outline f o r m as a guide,thus proving the validity of the said theory among the clinicians of U. P. College of Dentistry. Twenty-five clinicians qualified as subjects. Photographs of each subject's face and maxillary central incisors were taken and were developed into slides. These were projected on an onion skin paper and were classified under the following shapes: square,, square tapering , tapering, and ovoid. Results, using the chi--square test, showed that among the 25 subjects, only six had face forms similar to tooth forms. Thus, Williams' Law of Harmony is not valid among U.P. College of Dentistry clinicians and that the facial outline form cannot be used to predict the tooth form of the maxillary central incisors. The correct tooth form of the maxillary central incisors cannot be predicted by using only the face from as guide. Other factors still need to be considered like the sex and age of the patient. There is really no single system of selection which can guarantee perfection.